The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1186/s12906-019-2447-2
|View full text |Cite
|
Sign up to set email alerts
|

Manual therapy for the pediatric population: a systematic review

Abstract: BackgroundThis systematic review evaluates the use of manual therapy for clinical conditions in the pediatric population, assesses the methodological quality of the studies found, and synthesizes findings based on health condition. We also assessed the reporting of adverse events within the included studies and compared our conclusions to those of the UK Update report.MethodsSix databases were searched using the following inclusion criteria: children under the age of 18 years old; treatment using manual therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 62 publications
(200 reference statements)
2
47
0
5
Order By: Relevance
“…However, given the methodological limitations to studies included [ …] we consider these results to be preliminary” [ 91 ]. Finally, Parnell Prevost et al reviewed and critically appraised 50 studies of various designs dealing with manual therapy for a wide variety of pediatric conditions and concluded that the evidence was inconclusive but favorable for some non-musculoskeletal disorders including infantile colic (4 RCTs included), nocturnal enuresis (no RCTs included), sub-optimal infant breastfeeding (no RCTs included), respiratory, eyes, ears, nose and throat conditions (3 RCTs included) [ 43 ]. However, the review by Parnell Prevost et al suffers from significant methodological limitations [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given the methodological limitations to studies included [ …] we consider these results to be preliminary” [ 91 ]. Finally, Parnell Prevost et al reviewed and critically appraised 50 studies of various designs dealing with manual therapy for a wide variety of pediatric conditions and concluded that the evidence was inconclusive but favorable for some non-musculoskeletal disorders including infantile colic (4 RCTs included), nocturnal enuresis (no RCTs included), sub-optimal infant breastfeeding (no RCTs included), respiratory, eyes, ears, nose and throat conditions (3 RCTs included) [ 43 ]. However, the review by Parnell Prevost et al suffers from significant methodological limitations [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported on the effectiveness of manual therapy for infantile colic. Two studies reported a favourable outcome,36 37 four were inconclusive,32 38–40 one study showed no beneficial effects over the control arm41 and one study reported an unfavourable outcome 2. Most of the reviews for manual therapy graded the RCT studies as low quality.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed the systematic review by Prevost et al [ 1 ] and are concerned about its methodological quality. We critically appraised the systematic review using the Scottish Intercollegiate Guidelines Network (SIGN) criteria for systematic reviews.…”
Section: Introductionmentioning
confidence: 99%